(untitled) (Research, Society and Development, 2024)
Factors such as bird lineage, age, diseases, management, nutrition and environmental factors have an influence on egg quality. In this sense, the objective was to evaluate the external and internal quality of eggs from laying hens of the Embrapa 051 lineage raised in a free-range system in the final stage of production. Twelve eggs were randomly collected weekly from Embrapa 051 layers raised in a free-range system. The design used was completely randomized (DIC), consisting of 6 treatments (age of birds in weeks: 75,76,77,78,79 and 80) with 12 replications (eggs) each. The variables analyzed were the Haugh unit (UH), shell thickness (EC), egg weight (g), percentage of albumen (%A), yolk (%G) and shell (%C), yolk index (IG) and albumen (IA), shell color (CC) and yolk color (CG). Statistical analyzes were performed using analysis of variance and means were compared using the Tukey test at 5% significance. There was no significant difference (p>0.05) for egg weight, HU and percentages of albumen, yolk and shell between the ages evaluated. The GI, CG, EC and WC differed (p<0.05) between the ages assessed. The internal and external quality of eggs from Embrapa 051 layers in the final stage of production, at 75, 76, 77, 78, 79 and 80 weeks of age, raised in a free-range system are similar to each other and the eggs are classified as excellent quality (UH > 72).